2019
DOI: 10.1123/ijspp.2018-0365
|View full text |Cite
|
Sign up to set email alerts
|

Level Versus Uphill Economy and Mechanical Responses in Elite Ultratrail Runners

Abstract: Purpose: To examine the net oxygen cost, oxygen kinetics, and kinematics of level and uphill running in elite ultratrail runners. Methods: Twelve top-level ultradistance trail runners performed two 5-min stages of treadmill running (level, 0%, men 15 km·h−1, women 13 km·h−1; uphill, 12%, men 10 km·h−1, women 9 km·h−1). Gas exchanges were measured to obtain the net oxygen cost and assess oxygen kinetics. In addition, running kinematics were recorded with inertial measurement unit motion sensors on the wrist, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…This finding was in agreement with a study of a shorter range of Comrades Marathon [8], that had shown a sex difference of 8.4 % in performance and this difference decrease from 1994 to 2017, as well as with research on distance [14] and time-limited [33] ultra-marathons. Performance in ultra-marathon has been observed to depend on maximal oxygen uptake and body composition, and the sex difference in these variables might partially explain the respective difference in performance [34,35]. With regards to the variation of sex difference in performance by age group, the findings depended on performance level.…”
Section: Male Age Group Runners Were Faster Than Female Age Group Runnersmentioning
confidence: 98%
“…This finding was in agreement with a study of a shorter range of Comrades Marathon [8], that had shown a sex difference of 8.4 % in performance and this difference decrease from 1994 to 2017, as well as with research on distance [14] and time-limited [33] ultra-marathons. Performance in ultra-marathon has been observed to depend on maximal oxygen uptake and body composition, and the sex difference in these variables might partially explain the respective difference in performance [34,35]. With regards to the variation of sex difference in performance by age group, the findings depended on performance level.…”
Section: Male Age Group Runners Were Faster Than Female Age Group Runnersmentioning
confidence: 98%
“…Level and uphill oxygen cost of running (OCR, i.e., the oxygen consumption per unit of distance covered, expressed in mLO 2 •kg −1 •km −1 ) were shown to be positively correlated in elite trail runners (Willis et al, 2019), but not in their subelite counterparts (Balducci et al, 2016(Balducci et al, , 2017, and this point remains unclear in healthy people unaccustomed to inclined running. Moreover, whether downhill ECR is related to the level and uphill ECR remains an open question due to the scarcity of results on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Competitive runners are athletes that compete in a range of local, regional, national, or international championships, and can be defined by event level (e. g. international athletes or elite athletes) or by existing classification or ranking systems by their respective governing bodies [10,11]. Investigations in elite athletes often involve small sample sizes [17,47]. Race times compared to other competitors and position within a specific competition can give a further indication of the level of competitiveness of an athlete.…”
Section: Review Thiemementioning
confidence: 99%
“…However, this is not correct because each discipline has quite distinct characteristics in terms of distance, elevation change, terrain, environmental conditions, and "event culture" (e. g. individual race characteristics, competitiveness, and community involvement). There is also an abundance of different nomenclature and spelling used in scientific publications, such as: ultramarathon, ultra marathon, mountain ultra marathon, mountain ultramarathon, ultra-trail-marathon, ultra trail running, long distance trail running, and trail running ultramarathon [12][13][14][15][16][17]. As scientific interest in these activities grows, it becomes imperative to clarify the terms and develop a universal language for discussing these events to avoid research misinterpretation and miscommunication and apply it appropriately to the relevant running population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation